Association of Obstructive Sleep Apnea and Nocturnal Hypoxemia With the Circadian Rhythm of Myocardial Infarction - Xiaochen Liu; Bin Wang; Wen Hao; Yuyao Qiu; Qian Guo; Yingying Guo; Qingjie Xin; Jingyao Fan; Bin Que; Wei Gong; Wen Zheng; Xiao Wang; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The circadian rhythm of myocardial infarction (MI) in patients with obstructive sleep apnea (OSA) remains disputable and no studies have directly evaluated the relationship between nocturnal hypoxemia and the circadian rhythm of MI. The aim of the current study was to evaluate the association of OSA and nocturnal hypoxemia with MI onset during the night. Methods Patients with MI in the OSA‐acute coronary syndrome (ACS) project (NCT03362385) were recruited. The time of MI onset was identified by patient's report of the chest pain that prompted hospital admission. All patients underwent an overnight sleep study using a type III portable sleep monitoring device after clinical stabilization during hospitalization. The difference in circadian variation of MI onset was evaluated between patients with moderate/severe OSA and non/mild OSA and those with or without nocturnal hypoxemia. Nocturnal hypoxemia was evaluated using 3 variables, including oxygen desaturation index, minimum oxygen saturation, and total sleep time with saturation <90%. Results Among 713 patients enrolled, 398 (55.8%) had moderate/severe OSA (apnea‐hypopnea index ≥15 events·h − 1). Compared with the non/mild OSA group, the MI onset was significantly increased in the moderate/severe OSA group between midnight to 5:59 am in 6‐hour epochs analysis (26.9% versus 18.4%, P=0.008). Only in patients with both moderate/severe OSA and nocturnal hypoxemia, including oxygen desaturation index ≥15, minimum oxygen saturation ≤86%, and total sleep time with saturation <90% ≥2%, the incidence of MI onset between midnight to 5:59 am was significantly increased. Moderate/severe OSA (adjusted odds ratio 1.66 [95% CI, 1.13–2.43]; P=0.01) and nocturnal hypoxemia (oxygen desaturation index ≥15 model, adjusted odds ratio 1.80, [95% CI, 1.21–2.66]; minimum oxygen saturation ≤86% model, adjusted odds ratio 1.70 [95% CI, 1.16–2.47]; P=0.006; total sleep time with saturation <90% ≥2% model, adjusted odds ratio 1.54 [95% CI, 1.04–2.27]; P=0.03) significantly predicted MI occurrence from midnight to 6:00 am. Conclusions A peak of incident MI onset between midnight to 5:59 am was observed in patients with moderate/severe OSA, especially in those presenting with nocturnal hypoxemia.